Características clínicas y calidad de respuesta inicial a corticoterapia en pacientes con trombocitopenia inmune primaria - Díaz Salazar, Guido Enrique (2025)
Introduction. The first-line treatment for primary immune thrombocytopenia (ITP) is corticosteroids. Objective. To describe the clinical and demographic characteristics of patients with ITP and to explore the factors associated with the initial response under usual care conditions. Methods. We conducted a retrospective study at the Arzobispo Loayza National Hospital, including patients treated between 2023 and 2024. Response was defined as a platelet count ≥ 30 × 10⁹/L, more than double the baseline value, and absence of post-treatment bleeding; complete response was defined as a platelet count ≥ 100 × 10⁹/L and absence of post-treatment bleeding. Results. We analyzed 39 patients, of whom 84.6% were women, with a median age of 42 years; 25.6% had comorbidities, and 53.8% were overweight or obese. 61.5% achieved a response, and 53.8% achieved a complete response. Among those with comorbidities, the proportion of response was lower. Conclusions. Under routine conditions, first-line corticosteroid treatment led to a complete response in approximately half of the patients with ITP, and the initial response was influenced by the presence of comorbidities.